Production of Hyperpolarised 129Xe for NMR Spectroscopy and Imaging - Woolley, Elliot (2007)
Hyperpolarised 3He has been used extensively in the neutron community and for magnetic resonance imaging (MRI) of the lungs. 129Xe has many desirable advantages compared to 3He for NMR, namely its chemical sensitivity, solubility, adsorption capability and atmospheric abundance. In this work we present the design and construction of a 129Xe spin exchange polariser that operates at gas pressures between 0.6 and 3 bar. The design incorporates a novel Volume Holographic Grating (VHG) spectrally narrowed, high power laser diode device as the optical pump source for a continuous gas flow cylindrical polarisation cell. Nuclear polarisations of 34 +/- 3 % are achieved in 129Xe gas. Magnetisation production factors in excess of 80 % cm^3 min^-1 are achieved using a pseudo batch-flow operation method. Major parameters affecting 129Xe gas polarisation are discussed and the first measurements of cell heating from laser light absorption by Rb vapour are made. Hyperpolarised 129Xe gas produced from our system is imaged inside a low field, whole body MRI scanner. NMR measurements from inside a human lung are made using hyperpolarised 129Xe. Preliminary work on dissolved solution NMR is presented as are studies on the feasibility of using hyperpolarised 129Xe for porosity characterisation of porous media in low magnetic fields.